Single-Stage Revision Anterior Cruciate Ligament Reconstruction: Experience with 92 cases (41 elite athletes), Using an Algorithm. Issue 7 (31st July 2020) - Borque, Kyle; Jones, Mary; Ball, Simon; Williams, Andy; White, Nathan
Objectives: The increased prevalence of anterior cruciate ligament (ACL) reconstructions has led to an increased need for revision ACL reconstructions. Despite the lack of comparative literature, two-stage revisions are often undertaken under the pretense they are safer. Through careful patient selection, pre-operative planning, and meticulous attention to detail, single stage revisions can be performed with good outcomes, decreasing healthcare costs, morbidity and recovery time for the patient. The objective of this paper is to present an algorithm (Figure 1) to determine single-stage or two-stage approaches to ACL revision with good outcomes in recreational and elite athletes. Methods: All revision ACL reconstructions performed by the senior author from September 2009 to July 2016, with minimum two year follow-up, were retrospectively reviewed. Outcomes measured were: any further surgery, graft re-rupture, re-revision, Tegner score, and knee injury and osteoarthritis outcomes score (KOOS). For the elite athlete population, return to play time, duration and level compared to pre-injury were also determined. Results: Ninety-four procedures were performed in 93 patients. This included 41 in elite athletes. In this series only 2 (2%) two-stage procedures were undertaken. At an average of 4.3 years (range: 2-8.5 years) post surgery, there had been two re-revisions. There were two further instances of graft failure which had not been re-revised. The graft failure rate was therefore 4.3%. There were 17 subsequent procedures, including six arthroscopic partial meniscectomies, five removal of prominent implants, and one total knee arthroplasty. The average Tegner score was 8.2 preoperatively, and 7.1 at follow up. At follow up, the average KOOS scores were 79.3 for symptoms, 88.0 for pain, 94.2 for activities of daily living, 73.6 for sport, and 68.9 for quality of life. Thirty-six of 41 elite athletes returned to play, at an average of 338 days post surgery. At an average of 4.6 years, 29 were still playing professionally. Of these, 15 were at the same level, and 14 at a lower level. Five players returned to play but have since retired. This occurred at an average of 3.1 years post op, at an age of 30. Conclusion: Single stage ACL revisions can be performed reliably in the majority, but not all, patients with persistent or recurrent instability following failed ACL reconstruction with good clinical outcomes and return to play, even in the elite athletic population. Figure 1.